Mediation by Placental DNA Methylation of the Association of Prenatal Maternal Smoking and Birth Weight - Andrés Cárdenas; Sharon M. Lutz; Todd M. Everson; Patrice Perron; Luigi Bouchard; Marie‐France Hivert (2019)
Abstract Prenatal maternal smoking is a risk factor for lower birth weight. We performed epigenome-wide association analyses of placental DNA methylation (DNAm) at 720,077 cytosine-phosphate-guanine (CpG) sites and prenatal maternal smoking among 441 mother-infant pairs (2010–2014) and evaluated whether DNAm mediates the association between smoking and birth weight using mediation analysis. Mean birth weight was 3,443 (standard deviation, 423) g, and 38 mothers (8.6%) reported smoking at a mean of 9.4 weeks of gestation. Prenatal maternal smoking was associated with a 175-g lower birth weight (95% confidence interval (CI): −305.5, −44.8) and with differential DNAm of 71 CpGs in placenta, robust to latent-factor adjustment reflecting cell types (Bonferroni-adjusted P < 6.94 × 10−8). Of the 71 CpG sites, 7 mediated the association between prenatal smoking and birth weight (on MDS2, PBX1, CYP1A2, VPRBP, WBP1L, CD28, and CDK6 genes), and prenatal smoking × DNAm interactions on birth weight were observed for 5 CpG sites. The strongest mediator, cg22638236, was annotated to the PBX1 gene body involved in skeletal patterning and programming, with a mediated effect of 301-g lower birth weight (95% CI: −543, −86) among smokers but no mediated effect for nonsmokers (β = −38 g; 95% CI: −88, 9). Prenatal maternal smoking might interact with placental DNAm at specific loci, mediating the association with lower infant birth weight.